Advances in mechanical engineering : selected contributions from the Conference "Modern Engineering: Science and Education", Saint Petersburg, Russia, June 2016 /: selected contributions from the Conference "Modern Engineering: Science and Education", Saint Petersburg, Russia, June 2016. ([2017]) - Unknown
No abstract available